2003
DOI: 10.1161/01.str.0000063365.10841.43
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Stroke Incidence and Decreasing Case Fatality, 1989–1998

Abstract: Background and Purpose-Although the incidence of and mortality from myocardial infarction (MI) have declined in most industrialized countries, incidence studies of stroke have shown less consistent trends. This study examines time trends in the incidence of stroke and case fatality rates in relation to socioeconomic circumstances and history of MI. Methods-Stroke incidence in the city of Malmö, Sweden (250 000 citizens), has been continuously monitored since 1989.All patients 50 to 79 years of age who experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 54 publications
4
52
2
Order By: Relevance
“…7,24 Less obvious is the similar socioeconomic gradient we saw in both genders for ischemic stroke, because socioeconomic inequalities are usually stronger in men than in women. 25 Out-of-hospital mortality in women contributes more to total incidence than male out-of-hospital mortality.…”
Section: Cesaroni Et Al Inequalities In Stroke Incidence and Prognosismentioning
confidence: 87%
“…7,24 Less obvious is the similar socioeconomic gradient we saw in both genders for ischemic stroke, because socioeconomic inequalities are usually stronger in men than in women. 25 Out-of-hospital mortality in women contributes more to total incidence than male out-of-hospital mortality.…”
Section: Cesaroni Et Al Inequalities In Stroke Incidence and Prognosismentioning
confidence: 87%
“…This may be one reason why the incidence of stroke in Sweden has remained unaltered or tended to increase. 4,15 Poor hypertension control is a long-standing and problematic clinical issue. There is more than one explanation, such as the attitude of the patient toward treatment, the clinician's notion and behavior, patient-doctor relations, drug intolerance, resistant hypertension, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The annual incidence of stroke increased from 1989 to 1998 in men and women. 4 Because hypertension is regarded as the most important risk factor for stroke, its increasing incidence may be attributed to inadequate hypertension control. Few population-based studies have studied the incidence of stroke in relation to the quality of hypertension treatment.…”
mentioning
confidence: 99%
“…3 Furthermore, hospital discharge data will only identify patients admitted to the hospital with stroke. Several registry-based studies report that Ͼ90% of patients with stroke are managed in the hospital, 8,26 a figure that is similar in Scotland. 27 Several registry-based studies have reported a reduction in stroke severity over time 23,28 and hospitalization of milder strokes may distort trends in case-fatality.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…1,2 Although overall mortality from stroke is falling in western Europe and America, [3][4][5] trends in incidence are less clear and there are conflicting reports of stable, 6 increasing, 7,8 and decreasing rates. 5,9,10 Stroke is a disease of the elderly.…”
mentioning
confidence: 99%